The Relationship between Anxiety, Depression, and Vital Signs among Postpartum Mothers in Yogyakarta - Puspitasari, Reni; Haryanti, Priyani (Universitas Pendidikan Indonesia, 2021)
Introduction: After labor, mothers need good physiological and psychological adjustments. The inability to adapt to a new situation can result in mothers' psychological stress, eventually leading to postpartum crises and depression. If this incident is not handled, it can lead to serious mental health problems, especially postpartum psychosis to bipolar disorder. In depressed and anxious people, the body will secrete adrenal hormones, which cause vital signs such as blood pressure, body temperature, respiration, and pulse. Objectives: This study aims to find the relationship between anxiety, depression, and vital signs of postpartum mothers. Method: This study used qualitative with correlation cross-sectional design. The respondents were 60 postpartum mothers at 0-6 months postpartum in Yogyakarta recruited using purposive sampling techniques. The instrument used to measure postpartum maternal depression was The Back Depression Inventory version II and State Anxiety Inventory (STAI) to measure anxiety. Data analysis used Pearson to find the relationship between anxiety, depression, and vital signs. Results: The t-test analysis shows there were relationship between state and trait anxiety with a pulse (p-value = 0.00), respiration (p-value = 0.00), depression with a pulse (the p-value = 0.00) and respiration (p-value 0.00). Discussion: Anxiety and depression can be detected from the changes in the vital signs of postpartum mothers so that early detection by health workers can prevent anxiety and depression ABSTRAKPendahuluan : Setelah melahirkan ibu membutuhkan adaptasi baik fisiologis maupun psikologis. Ketidak mampuan ibu beradaptasi dengan peran baru akan menyebabkan tekanan psikologis yang bisa menyebabkan kecemasan dan depresi postpartum. Jika kejadian ini tidak ditangani maka dapat mengakibatkan masalah kejiwaan yang serius khususnya postpartum psychosis hingga bipolar. Pada orang depresi dan cemas, tubuh akan mensekresikan hormon adrenal yang mengakibatkan tanda-tanda vital seperti tekanan darah, suhu tubuh, pernafasan, dan nadi. Tujuan : Tujuan dari penelitian ini adalah mengetahui hubungan antara ansietas dan tingkat depresi dengan vital signs ibu postpartum. Metode: Penelitian ini menggunakan kuantitatif dengan metode korelasi cross-sectional. Responden sebanyak 60 ibu postpartum 0-6 bulan yang berdomisili di Yogyakarta ditentukan dengan teknik purposive sampling. Instrumen yang digunakan untuk mengukur depresi ibu postpartum adalah The Back Depression Inventory versi II dan pengukuran kecemasan ibu postpartum menggunakan State Anxiety Inventory (STAI). Analisa data menggunakan pearson untuk mencari hubungan antara ansietas, depresi dengan tanda-tanda vital. Hasil: analisa t test membuktikan terdapat hubungan antara ansietas dasar dan sesaat dengan nadi (p value 0.00) dan pernafasan (p value 0.00). Terdapat pula hubungan antara depresi dengan nadi ibu postpartum (p value 0.00) dan pernafasan (p value 0.00). Diskusi : kecemasan dan depresi dapat dideteksi dari adanya perubahan tanda-tanda vital ibu postpartum, sehingga deteksi awal oleh petugas kesehatan dapat mencegah terjadinya kecemasa dan depresi.